Divergent properties and independent regulation of striatal dopamine and GABA co-transmission - Sarah M. Zych; Christopher P. Ford (Cell Reports, 2022)
Summary: Substantia nigra pars compacta (SNc) dopamine neurons play a key role in regulating the activity of striatal circuits within the basal ganglia. In addition to dopamine, these neurons release several other transmitters, including the major inhibitory neurotransmitter γ-aminobutyric acid (GABA). Both dopamine and GABA are loaded into SNc synaptic vesicles by the vesicular monoamine transporter 2 (VMAT2), and co-release of GABA provides strong inhibition to the striatum by directly inhibiting striatal medium spiny projection neurons (MSNs) through activation of GABAA receptors. Here, we found that despite both dopamine and GABA being co-packaged by VMAT2, the properties of transmission, including Ca2+ sensitivity, release probability, and requirement of active zone scaffolding proteins, differ between the two transmitters. Moreover, the extent by which presynaptic neuromodulators inhibit co-transmission also varied. Differences in modulation and the mechanisms controlling release allow for independent regulation of dopamine and GABA signals despite both being loaded via similar mechanisms.